A survey of Canadian healthcare professionals' practices regarding reactive balance training. (3rd July 2021) - Mansfield, Avril; Danells, Cynthia J.; Inness, Elizabeth L.; Musselman, Kristin; Salbach, Nancy M.
ABSTRACT: Background : Perturbation-based balance training (PBT) is a relatively new type of balance training that aims to improve control of reactions to a loss of balance. This study aimed to determine the prevalence of use of PBT in clinical practice, and the most significant barriers and facilitators to implementing PBT in practice. Methods : Health-care professionals across Canada (primarily physiotherapists and kinesiologists) who provide balance training to individuals with balance impairments and/or increased fall risk completed a questionnaire that asked about knowledge and use of PBT in practice. Results : Overall, 76.3% of participants (299/392) reported that they had used PBT in their practices, with 22.4% (88/392) reporting regular PBT use. Lack of knowledge of PBT appeared to be the most significant barrier for those not currently using PBT in their practices, whereas individuals who were familiar with PBT and open to using it in practice experienced barriers related to training, knowledge, human resources, client characteristics, and the practice setting. More than 90% of respondents were interested in learning more about almost all aspects of PBT. Conclusions : These findings could be used to inform development of future educational strategies to increase uptake of PBT in rehabilitation practice.